Dyskerin and TERC expression may condition survival in lung cancer patients - Penzo, Marianna (Oncotarget, 2015)
Dyskerin mediates both the modification of uridine on ribosomal and small nuclear RNAs and the stabilization of the telomerase RNA component (TERC). In human tumors dyskerin expression was found to be associated with both rRNA modification and TERC levels. Moreover, dyskerin overexpression has been linked to unfavorable prognosis in a variety of tumor types, however an explanation for the latter association is not available. To clarify this point, we analyzed the connection between dyskerin expression, TERC levels and clinical outcome in two series of primary lung cancers, differing for the presence of TERC gene amplification, a genetic alteration inducing strong TERC overexpression. TERC levels were significantly higher in tumors bearing TERC gene amplification (P = 0.017). In addition, the well-established association between dyskerin expression and TERC levels was observed only in the series without TERC gene amplification (P = 0.003), while it was not present in TERC amplified tumors (P = 0.929). Similarly, the association between dyskerin expression and survival was found in cases not bearing TERC gene amplification (P = 0.009) and was not observed in TERC amplified tumors (P = 0.584). These results indicate that the influence of dyskerin expression on tumor clinical outcome is linked to its role on the maintenance of high levels of TERC.